Demonstrating the Utility of New Linked National Health Survey and Administrative Data: Secondary CVD Prevention in The Community - Danielle Butler; Hsei Di Butler; Ellie Paige; Lynelle Moon; Emily Banks; Rosemary J Korda (International Journal of Population Data Science, 2020)
Introduction Cardiovascular events are largely preventable though access to timely quality primary health care and use of guideline-recommended medication. However, around half of Australians with cardiovascular disease (CVD) are not receiving best practice treatment. This study aims to identify factors associated with under treatment, using National Health Survey (NHS) linked for the first time to administrative health data.